Analisis Naratif: Perspektif Partai Oposisi terhadap Diberhentikannya Tayangan Indonesian Lawyer Club TV One dalam Menyikapi Isu Demokrasi Indonesia - Arizal Arizal; Banda Napitulu; Dita Lestari; Lody Winata; Lucytha Carolina; Muzahid Akbar Hayat (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Mass media has had a huge impact on the history of human life. The Indonesia Lawyers Club (ILC) talk show hosted by senior journalist Karni Ilyas is rumored to have stopped airing. This drew a response from various politicians including opposition politicians who were very sorry for not re-airing the event as a forum for democratic aspirations that were sufficient transparency in the show to the public. The purpose of this study is to find out the state of democracy in Indonesia through the media of criticism by analyzing how perspective through the perspective of narrative analysis of statements of opposition party politicians regarding the dismissal of Indonesian Lawyer Club shows on TV One in addressing the issue of Indonesian democracy. The method used in this study is with a qualitative approach with a narrative analysis framework method by analyzing the content of news. The results stated that Fadli revealed this news is sad news and bad news for democracy. Because there are currently very few platforms that provide freedom of expression. In conclusion, fadli's allegations were corroborated by Karli Ilyas' answer to Mahfud MD's question about intimidation in various directions. At the same time, the mass media plays an important role in functioning the democratic government to the people.